Cost of capital changes, the quality of trading information and market architecture. Issue 4 (December 2016) - Chelley-Steeley, Patricia L.; Lambertides, Neophytos
Abstract: In this paper, we examine whether there are cost of capital changes for stocks that migrate from a dealer to an auction trading system. We are motivated to undertake this research since there is a link between information quality and the architecture of a trading system. Moreover, recent research, such as that by Lambert, Leuz, and Verrecchia (2007) suggests a connection between the quality of information and the cost of capital which suggests there may be a link between the trading system and the cost of capital. An opportunity to observe whether a change to the trading system influences the cost of capital presented itself in 2003, when stocks began to migrate away from SEAQ, the more opaque trading system, onto the more transparent SETSmm trading system. We use the Fama-French and implied cost of capital models to show that the cost of capital fell for firms migrating from the dealer market SEAQ to the hybrid auction system SETSmm. We estimate that the average change in Fama-French market beta equates to a reduction in the cost of capital of about 0.6%.